Legalitas Pendaftaran Investasi Asing pada Sistem Online Single Submission Risk Based Approach (Oss-RBA) di Indonesia - Jesycha Nasrani Lussy; Jeffry A. Ch. Likadja; Elisabeth N.S. Bota Tukan (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This study aims to find out and analyze the legality of foreign investment registration in the online single submission risk based approach (Oss-RBA) system in Indonesia. This research is a normative research using primary, secondary and tertiary legal materials collected by tracing or searching and documentation studies, the legal materials that have been collected are processed and analyzed in several stages, namely inventory, identification, classification and systematization. The results of the study show that (1) Law Number 25 of 2007 concerning investment has been in compliance with TRIMs. (2) Foreign investment business licenses in the Oss-RBA system are not considered to violate TRIM's because they are not regulated in the illustration of the violation of the TRIM's agreement.